2000
DOI: 10.1093/qjmed/93.6.341
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol hepatotoxicity and alcohol consumption in deliberate and accidental overdose

Abstract: We studied the relationship between alcohol consumption and hepatotoxicity related to paracetamol ingestion both in cases of overdose with suicidal intent and in cases where paracetamol was apparently taken for therapeutic reasons. In a retrospective study of 553 patients admitted to a specialist liver unit between January 1987 and December 1993 with paracetamol-induced hepatotoxicity, there was no difference in the severity of the hepatotoxicity following either a deliberate or an inadvertent overdose. Heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 57 publications
2
50
0
7
Order By: Relevance
“…Because the subjects with ALF reporting use of Յ4 g acetaminophen per day were often alcohol abusers (65%) and the amount of daily alcohol consumed was greater than that reported by patients who admitted to taking Ͼ4 g acetaminophen per day (data not shown), ethanol may still serve as an important co-factor in these lower-dose subjects. 4,6,13,24,[34][35][36] The overall transplant-free survival rate of 65% in acetaminophen subjects is comparable to that of prior studies and continues to be more favorable than that observed for most other ALF causes. 13,37,38,39 The use of the King's criteria at admission to predict outcome was inaccurate, and use of the APACHE II provided a more accurate of assessment outcome.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Because the subjects with ALF reporting use of Յ4 g acetaminophen per day were often alcohol abusers (65%) and the amount of daily alcohol consumed was greater than that reported by patients who admitted to taking Ͼ4 g acetaminophen per day (data not shown), ethanol may still serve as an important co-factor in these lower-dose subjects. 4,6,13,24,[34][35][36] The overall transplant-free survival rate of 65% in acetaminophen subjects is comparable to that of prior studies and continues to be more favorable than that observed for most other ALF causes. 13,37,38,39 The use of the King's criteria at admission to predict outcome was inaccurate, and use of the APACHE II provided a more accurate of assessment outcome.…”
Section: Discussionsupporting
confidence: 68%
“…The rate of unintentional overdose was estimated to be 31% in Australia, and nonsuicidal overdoses are only rarely reported in the United Kingdom and Europe. [24][25][26] Single timepoint ingestions with suicidal intent constituted 70% of all hospitalized subjects in one U.S. series, but these subjects frequently presented early after ingestion when use of NAC would be effective, so that few developed encephalopathy and only 2% died. 7 In the current series, in which cases were limited to those subjects reaching the threshold of encephalopathy, the mortality rate was higher (approximately 29%) and similar for the intentional and unintentional groups.…”
Section: Discussionmentioning
confidence: 99%
“…There were no randomized controlled (level 1b) trials evaluating the efficacy of acetylcysteine in the out-ofhospital setting. Many observational studies reported the use of acetylcysteine in the out-of-hospital setting but did not explicitly give information on its effectiveness and so they are not specifically addressed here (3,44,51,53,54,67,72,119,120). In addition, multiple case reports and case series (level 4) were reported in which the efficacy of acetylcysteine could not be assessed.…”
Section: Detoxification Of Acetaminophen Metabolite (Napqi)mentioning
confidence: 99%
“…Thus, alcohol induced dose dumping (AIDD) can be defined as the rapid unintended release of a large amount of drug from a MR dosage form resulting from an accidental misuse or from intentional abuse of alcohol with the drug. Co-consumption with alcohol can complicate matters because it may influence the absorption, metabolism and excretion of drugs (Makin & Williams 2000;Weathermon & Crabb 1999).…”
Section: Introductionmentioning
confidence: 99%